Application of the Uniform Data Set version 3 tele-adapted test battery (T-cog) for remote cognitive assessment preoperatively in older adults - Rockholt, Mika M.; Wu, Rachel R.; Zhu, Elaine; Perez, Raven; Martinez, Hamleini; Hui, Jessica J.; Commeh, Ekow B.; Denoon, Romario B.; Bruno, Gabrielle; Saba, Braden V.; Waren, Daniel; O'Brien, Courtney; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionOlder adults undergoing surgery are at risk of postoperative neurocognitive disorders, prompting the need for preoperative cognitive screening in this population. Traditionally, cognitive screening has been conducted in-person using brief assessment tools such as the Montreal Cognitive Assessment (MoCA) or the Mini-Mental State Examination (MMSE). More comprehensive test batteries, such as the Uniform Data Set (UDS) Neuropsychological Battery, and its remote testing version, the Uniform Data Set version 3 tele-adapted test battery (UDS v3.0 T-cog), have been developed to assess cognitive decline in normal aging and disease conditions, but have not been applied in the perioperative setting.MethodsWe assessed the feasibility of using this remote UDS v3.0 T-cog battery for preoperative cognitive assessment in 81 older adults 65+ scheduled for lower extremity joint replacement surgery.ResultsOur results indicate that the UDS v3.0 T-cog achieves 99% completion rates and demonstrates high patient satisfaction. Further, we found 28% of subjects were cognitively impaired in this patient cohort.DiscussionThese findings suggest that the UDS v3.0 T-cog is a feasible tool for assessing cognitive function in the older adult perioperative population. To our knowledge, this is the first study to apply this comprehensive remote test battery in the preoperative setting.